SOME COMMENTS ON THE LEARNING OF ARABIC (Archive of Conferences, 2020)
It is known that there are different methods of teaching Arabic, but the initial stage of learning Arabic is the most important. All the knowledge acquired by students during this period will determine the success of learning in future periods. Particular attention should be paid to the phonetic part of the study, because at the same time the correct pronunciation of sounds will be etched in the memory for a lifetime.